2020
DOI: 10.1002/jper.20-0138
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the periodontal disease—ischemic stroke link

Abstract: Multiple risk factors are associated with ischemic stroke. Here, we highlight studies indicating that periodontal disease significantly increases the risk of both primary ischemic stroke and subsequent cardiovascular events. Additionally, studies have shown an association between periodontal disease and multiple causes of ischemic stroke. Finally, we describe an ongoing clinical trial testing the benefit of periodontal disease treatment as a strategy to reduce risk for recurrent cardiovascular events in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
2
0
2
Order By: Relevance
“…Prior studies have reported an association between PD and ECAS as well as aortic arch atherosclerosis [16, 18]. However, limited data to date support the PD-ICAS link [30]. To our knowledge, this may be one of the first studies to report an association between PD measured as specific PD stages and ICAS-driven ischemic stroke.…”
Section: Discussionmentioning
confidence: 59%
“…Prior studies have reported an association between PD and ECAS as well as aortic arch atherosclerosis [16, 18]. However, limited data to date support the PD-ICAS link [30]. To our knowledge, this may be one of the first studies to report an association between PD measured as specific PD stages and ICAS-driven ischemic stroke.…”
Section: Discussionmentioning
confidence: 59%
“…This report opens the prelude to studying the relationship between periodontitis and ischemic stroke. Over the past 30 years, several case-control studies, cross-sectional studies, and cohort studies have confirmed this association ( 8 12 ). A 15-year follow-up community cohort study of 10,362 stroke-free participants found an independent association between periodontal disease and stroke risk, and that regular oral periodontal care reduced the risk of stroke ( 13 ).…”
Section: Introductionmentioning
confidence: 82%
“…A contribuição da periodontite para a ocorrência do acidente vascular cerebral isquêmico pode ser indiretamente mediante mecanismos inflamatórios (Sen et al, 2018;O'Boyle et al, 2020). Doenças inflamatórias crônicas, incluindo gengivite e periodontite, vêm sendo demonstradas como fatores envolvidos no desenvolvimento de doenças cardiovasculares e risco de acidentes vasculares cerebrais (Beck et al, 1996;Beck, & Offenbacher, 2001;Scannapieco, Bush, & Paju, 2003;Chi et al, 2019;Lin et al, 2019;O'Boyle et al, 2020;Sen, & Mascari, 2020). Estudos ressaltam que a periodontite e a perda dentária estão associados com os índices de ocorrência de AVC isquêmicos (Söder, Meurman, & Söder, 2015;Sen, & Mascari, 2020).…”
Section: Introductionunclassified
“…Doenças inflamatórias crônicas, incluindo gengivite e periodontite, vêm sendo demonstradas como fatores envolvidos no desenvolvimento de doenças cardiovasculares e risco de acidentes vasculares cerebrais (Beck et al, 1996;Beck, & Offenbacher, 2001;Scannapieco, Bush, & Paju, 2003;Chi et al, 2019;Lin et al, 2019;O'Boyle et al, 2020;Sen, & Mascari, 2020). Estudos ressaltam que a periodontite e a perda dentária estão associados com os índices de ocorrência de AVC isquêmicos (Söder, Meurman, & Söder, 2015;Sen, & Mascari, 2020). Devido a essa intima relação se devem estabelecer os grupos populacionais de risco para a doença periodontal, e que esta inflamação crônica possa aumentar a probabilidade de ocorrência do Acidente Vascular Cerebral (AVC) (Díaz, & Aguiar, 2016;Sen et al, 2018).…”
Section: Introductionunclassified